The influence of Burpee on the volume of attention of schoolchildren (Bangladesh Journal of Medical Science, 2023)
Objectives: to determine the influence of the «Burpee» exercise on the indicators of endurance and volume of attention in children aged 15-16.Methods: the pedagogical experiment was carried out on the basis of a comprehensive school, the city of Kirov, Russia. The study involved children 15-16 years old in the amount of 52 people. During the study period, 30 physical education lessons were held in each class. Children from the control group were engaged in the usual program, and children from the experimental group additionally performed the «Burpee» exercise. Endurance in children was determined by the test «2000 m», and the volume of attention was determined by the test «Schulte Tables». The study used Excel and BioStat to determine Student’s T-test.Results: after the pedagogical experiment, the indicators in the control group in the «2000 m» test improved by 1.9% (p>0.05), and in the «Schulte Tables» by 4.8% (p>0.05). In the experimental group, the performance improved significantly in the «2000 m» test by 9% (p